2010
DOI: 10.1002/dvdy.22444
|View full text |Cite
|
Sign up to set email alerts
|

Dermoskeleton morphogenesis in zebrafish fins

Abstract: Zebrafish fins have a proximal skeleton of endochondral bones and a distal skeleton of dermal bones. Recent experimental and genetic studies are discovering mechanisms to control fin skeleton morphogenesis. Whereas the endochondral skeleton has been extensively studied, the formation of the dermal skeleton requires further revision. The shape of the dermal skeleton of the fin is generated in its distal growing margin and along a proximal growing domain. In these positions, dermoskeletal fin morphogenesis can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
59
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(70 citation statements)
references
References 112 publications
9
59
0
2
Order By: Relevance
“…One substantial difference between Class 2 and Class 3 mosaics was that the latter had a more punctate pattern of mCherry + cells that were concentrated at lepidotrichia joints. Since intra-ray fibroblasts and osteoblasts reside within and adjacent to lepidotrichia, respectively (Akimenko et al, 2003; Poss et al, 2003; Mari-Beffa and Murciano, 2010), we sectioned the same fins photographed in Figure 1G–H* and stained them with antibodies against osteoblast specific proteins. We observed that the Class 3 cells shown in Figure 1H and H* were positive for the osteoblast marker zns-5 (Johnson and Weston, 1995; Wills et al, 2008 and Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One substantial difference between Class 2 and Class 3 mosaics was that the latter had a more punctate pattern of mCherry + cells that were concentrated at lepidotrichia joints. Since intra-ray fibroblasts and osteoblasts reside within and adjacent to lepidotrichia, respectively (Akimenko et al, 2003; Poss et al, 2003; Mari-Beffa and Murciano, 2010), we sectioned the same fins photographed in Figure 1G–H* and stained them with antibodies against osteoblast specific proteins. We observed that the Class 3 cells shown in Figure 1H and H* were positive for the osteoblast marker zns-5 (Johnson and Weston, 1995; Wills et al, 2008 and Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The caudal fin is a favored model of regeneration since it is easy to amputate, is not required for viability, regenerates all parts of its anatomy, and completely regenerates in a short time frame (2 weeks). The zebrafish caudal fin is composed of bony ray segments, known as lepidotrichia that are joined together by ligaments (Mari-Beffa et al, 2007; Mari-Beffa and Murciano, 2010). These rays form by direct mineralization coordinated by osteoblasts, specialized cells that deposit bone matrix (Karsenty et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous pathways regulate positioning and outgrowth of these rays and the joints within the rays (Marí-Beffa & Murciano, 2010; Sims, Eble, & Iovine, 2009). Early proximo-distal patterning in the fin bud, largely controlled by Fgf signaling, is thought to establish a “prepattern” for ray positioning.…”
Section: Local Mechanisms Of Morphogenetic Changesmentioning
confidence: 99%
“…In future studies, it should be interesting to examine whether the observed thermally induced plasticity of the caudal fin is mediated by alterations of the expression of genes like fgfs, shh, bmp2b , and cx43 , which are involved in the growth and differentiation of the caudal‐fin rays (Govindan & Iovine, ; Lee, Grill, Sanchez, Murphy‐Ryan, & Poss, ; Quint et al, ; Sims, Eble, & Iovine, ; Wills, Kidd, Lepilina, & Poss, ). Such alterations might occur at the level of individual genes, or be part of a thermally induced modification of the “positional identity” gradient, a prespecification gradient that controls the position‐dependent growth and differentiation of fin rays (Mari‐Beffa & Murciano, ; Rabinowitz et al, ).…”
Section: Discussionmentioning
confidence: 99%